Between Past and Future - 1/6
Recording of the media panel (“1989 and Its Aftermath through the Eyes of the Media”) part of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference held at CEU in March 1999. The debate between the members of the panel is followed by a debate between the journalists and the audience, including conference participants István Rév, Timothy Garton Ash and Tamás Gáspár Miklós. The members of the panel are R. W. Apple Jr. (Chief Correspondent, “New York Times”), Barrie Dunsmore (Former Senior Correspondent, ABC News), James Carney (Political Correspondent, “Time Magazine”), Flora Lewis (Senior Columnist, “New York Times” Syndicate), Ambassador Richard Holbrooke (U.S. Special Envoy to Yugoslavia) and György Bolgár (Journalist and Broadcaster, Hungarian Radio). The moderator of the discussion is Kati Marton.